The Involvement of Iron in Traumatic Brain Injury and Neurodegenerative Disease - Daglas, Maria; Adlard, Paul A. (Frontiers in Neuroscience, 2018)
Traumatic brain injury (TBI) consists of acute and long-term pathophysiological sequelae that ultimately lead to cognitive and motor function deficits, with age being a critical risk factor for poorer prognosis. TBI has been recently linked to the development of neurodegenerative diseases later in life including Alzheimer’s disease, Parkinson’s disease, chronic traumatic encephalopathy, and multiple sclerosis. The accumulation of iron in the brain has been documented in a number of neurodegenerative diseases, and also in normal aging, and can contribute to neurotoxicity through a variety of mechanisms including the production of free radicals leading to oxidative stress, excitotoxicity and by promoting inflammatory reactions. A growing body of evidence similarly supports a deleterious role of iron in the pathogenesis of TBI. Iron deposition in the injured brain can occur via haemorrhage/ microhaemorrhages (heme-bound iron) or independently as labile iron (non-heme bound), which is considered to be more damaging to the brain. This review focusses on the role of iron in potentiating neurodegeneration in TBI, with insight into the intersection with neurodegenerative conditions. An important implication of this work is the potential for therapeutic approaches that target iron to attenuate the neuropathology/phenotype related to TBI and to also reduce the associated risk of developing neurodegenerative disease.